Current Challenges of Cold Brew Coffee—Roasting, Extraction, Flavor Profile, Contamination, and Food Safety - Raven Kwok; Kenny Lee Wee Ting; Steffen Schwarz; Linda Claassen; Dirk W. Lachenmeier (Challenges, 2020)
Cold brew coffee has emerged as a new trend over the last decade. However, “cold brew” is an extraction style of ground roasted coffee with water at lower than body temperature (typically 8 °C or room temperature), rather than a beverage per se. Cold brew extraction poses several challenges, including the need for specific optimization depending on the multiple influences of coffee variety and processing, roast degree, grinding, dosage, water composition, turbulence, brew system (drip, immersion etc.), time and temperature, and their interactions. While cold brew is typically characterized by a floral sweetness, over-extraction may lead to abundant acidity and bitterness. To avoid this, an extraction degree of 70% was suggested using shorter time frames (i.e., 2 h at 15 °C with 80 g/L coffee for optimized medium roast profiles). Due to the lack of sterilizing temperatures during preparation, cold brew is significant in the coffee sector because hygiene and food safety requirements pose specific challenges. To avoid microbiological contamination and deterioration in quality, cold brew should be as freshly prepared as possible and shelf-life should be minimized.